Electrochemical Detection of Steroid Hormones Using a Nickel‐Modified Glassy Carbon Electrode. Issue 10 (15th September 2014) - Muna, Grace W.; Partridge, Michael; Sirhan, Hala; VerVaet, Bridget; Guerra, Nigel; Garner, Holly
Abstract This paper demonstrates the development of an analytical method for detecting steroid hormones by coupling HPLC to electrochemical detection, using a nickel‐modified glassy carbon electrode. The method was evaluated in terms of sensitivity, linear dynamic range, limit of detection, and response stability. The developed method exhibited good figures of merit for the steroid hormones studied with no evidence of electrode fouling. As an example, the limit of detection (S/N=3) for E3 was 0.10 µM and the response precision (n=5) was 0.6 %. The application of the method for the analysis of a real river water sample is demonstrated.